Clinical Profile of Children with Pyelonephritis and Cystitis in Dr. Soetomo General Academic Hospital, Surabaya - Lutifta Hilwana; Ninik Asmaningsih Soemyarso; Atika Atika (Universitas Airlangga, 2023)
Highlights:1. In patients younger than one year old, cystitis was more frequent in boys. Meanwhile, in patients aged 1-5, girls were more frequent in pyelonephritis and cystitis.2. In pyelonephritis, all patients had fever, followed by diarrhea and lethargy.3. Urinary symptoms, such as dysuria and hematuria, were more frequent in cystitis than in pyelonephritis. AbstractIntroduction: Urinary tract infection (UTI) is a common infection in children. Prompt diagnosis and treatment of this infection are important to prevent further damage to the kidney. This study aimed to examine the clinical profile of children with pyelonephritis and cystitis in Dr. Soetomo General Academic Hospital, Surabaya.Methods: This was a descriptive study conducted in Dr. Soetomo General Academic Hospital, Surabaya, from June 2013 until December 2015, using secondary data and presented by percentage. Samples included in this study were children aged two months to five years old with UTI as a primary or secondary diagnosis of diarrhea and had urine culture results ≥ 105 CFU/ml.Results: There were 30 patients with pyelonephritis and 27 patients with cystitis. The prevalence of pyelonephritis was 0.285% and of cystitis was 0.247%. In pyelonephritis patients younger than one-year-old, boys and girls were equal. However, boys (60%) were more frequent in cystitis patients. In both pyelonephritis and cystitis patients aged 1-5, girls were more frequent (56.3%; 64.7%). In pyelonephritis patients, all patients were found with fever, followed by diarrhea (60%) and lethargy (56.7%) as the two most common symptoms. The two most common symptoms in cystitis patients were lethargy (44.4%) and irritability (33.3%). Urinary symptoms, such as dysuria and hematuria, were more frequent in cystitis (11.1%; 7.4%) patients than in pyelonephritis patients.Conclusion: Boys were more frequent to suffer urinary tract infections. Systemic symptoms were frequently found in pyelonephritis patients, while urinary symptoms were more frequent in cystitis patients.